A systematic review of regional hyperthermia therapy in bladder cancer. (18th May 2016) - Longo, Thomas A.; Gopalakrishna, Ajay; Tsivian, Matvey; Van Noord, Megan; Rasch, Coen R.; Inman, Brant A.; Geijsen, Elisabeth D.
Abstract: Context: Bladder cancer therapy remains suboptimal as morbidity and mortality remain high amongst those with non-muscle-invasive and muscle-invasive disease. Regional hyperthermia therapy (RHT) is a promising adjunctive therapy being tested in multiple clinical contexts. Objective: The aim of this study was to systematically review the literature on the efficacy and toxicity of RHT. Evidence acquisition: This systematic review was registered with the PROSPERO database (Registration number: CRD42015025780) and was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. We queried PubMed, EMBASE, and Cochrane libraries. Two reviewers reviewed abstracts independently and a third reviewer arbitrated disagreements. The last search was performed on 28 August 2015. A descriptive analysis was performed and quality assessment was conducted using the Newcastle-Ottawa Quality Assessment Scale for observational studies, and the Cochrane Risk of Bias Assessment Tool for trials. Evidence synthesis: We identified 859 publications in the initial search, of which 24 met inclusion criteria for full-text review. Of these, we were able to obtain data on the outcomes of interest for 15 publications. Conclusions: The review underscores the limited nature of the evidence; definitive conclusions are elusive. However, the promising results of RHT in the setting of intravesical chemotherapy, chemotherapy and radiotherapy show a trend towards legitimate efficacy.